The Benefit of Society for Antibiotic Growth Factors Using Probiotics and In Vitro Leaf Extracts - Balgis Al Basyarahil; Mohammad Anam Al Arif; Bambang Prajogo E.W (Budapest International Research and Critics University, 2022)
The increasing demand for chicken meat resulted in increased chicken production. To determine the bland power of probiotic antibacterial activity (B. subtilis and L. acidophilus) against E. coli growth through Minimum Inhibitory Concentration (MIC) and Minimum Bacterisidal Concentration (MBC), to determine the bland force of antibacterial activity of ethanol extract E. scaber linn against E. coli growth through Minimum Inhibitory Concentration (MIC) and Minimum Bacterisidal Concentration (MBC) and to identify the activity of probiotics and ethanol extract E. scabber Linn as an alternative to antibiotic growth promoters. This study is an experimental descriptive study. The dried samples of tapak liman (Elephantophus scaber L.) leaves were weighed as much as 700 grams and put into a maceration container. Simplicia was macerated using 2 types of solvents, namely 75% ethanol and 96% ethanol, so that 2 types of ethanol extract were obtained. Based on the results of disk diffusion and optical density tests analyzed with statistical testing. For data from the results of the disk diffusion method analyzed with One-Way Analysis of Variance (ANOVA) and continued with Post-Hock, data from the analysis with dilution methods were analyzed with Kruskal-Wallis and continued with Mann-Whitney, while MBC dinalysis results were descriptive. Research results: Apart from green tea and reeds, other plants such as tapak liman also have antibacterial activity. The combination of tread liman with chloramphenicol against E. coli has additive value. Previous tests used extracts from tapak liman which were still in the form of crude extracts, namely alkaloids, saponins, terpenoids, flavonoids, steroids, tannins and quinones that would interact with antibiotics that have antibacterial activity (Dwary et al., 2020), because E.scaber contains compounds flavonoids, tannins, saponins and alkaloids. According to the results of the study, the results of the MIC showed 10% for Gynura Procumbens leaf extract, and 30% for E. scaber leaves. The results of the LDH study showed that there was an inhibition of 96% ethanol extract of G. procumbens and E. scaber leaves on the growth of S. thypi bacteria with the inhibitory power in the weak category. For G. procumbens leaf extract the highest LDH was 4.5 mm at 30% concentration and the highest LDH for E. scaber leaf extract was 4.3 mm at 50% extract concentration